Effects of congruent and incongruent appetitive and aversive well-being comparisons on depression, post-traumatic stress, and self-esteem - Emily N. Keppler; Nexhmedin Morina; Pascal Schlechter (European Journal of Psychotraumatology)
Background: People compare their current well-being to different comparison standards (e.g. social or temporal comparisons). These standards are considered as aversive if perceived as threatening to self-motives or appetitive if perceived as consistent with self-motives. However, it remains unknown whether the congruence (vs. incongruence) of aversive and appetitive well-being comparisons (high levels of both vs. preponderance of aversive comparisons over appetitive comparisons) is differentially related to symptoms of depression and post-traumatic stress disorder (PTSD) and self-esteem.Methods: We conducted response surface analysis (RSA) on data from a study with two-timepoints three months apart (N = 921). RSA tests whether the degree of (in-)congruence of two variables is positively or negatively related to an outcome variable. Here, baseline aversive and appetitive well-being comparisons (comparison frequency, discrepancy, and affective impact) served as the two predictor variables, while depression, PTSD, and self-esteem three months later served as outcomes.Results: Findings partially confirmed our hypotheses. Congruently high (vs. low) levels of aversive and appetitive comparison frequency and discrepancy predicted more depressive/PTSD symptoms and lower self-esteem. Some evidence indicated more pronounced depressive symptoms and lower self-esteem (but not PTSD) for the preponderance of aversive over appetitive comparisons.Conclusions: The effects of congruent and incongruent aversive and appetitive comparisons as well as a potentially more crucial role of aversive than appetitive well-being comparisons in depression and self-esteem align with comparison theory.